Stellar Activity Cycles in a Model for Magnetic Flux Generation and Transport - Işık, Emre (Cambridge Univ Press, The Pitt Building, Trumpington St, Cambridge Cb2 1Rp, Cambs, England, 2012)
We present results from a model for magnetic flux generation and transport in cool stars and a qualitative comparison of models with observations. The method combines an alpha Omega-type dynamo at the base of the convection zone, buoyant rise of magnetic flux tubes, and a surface flux transport model. Based on a reference model for the Sun, numerical simulations were carried out for model convection zones of G- and K-type main sequence and subgiant stars. We investigate magnetic cycle properties for stars with different rotation periods, convection zone depths, and dynamo strengths. For a Sun-like star with P-rot=9 d, we find that a cyclic dynamo can underly an apparently non-cyclic, 'flat' surface activity, as observed in some stars. For a subgiant K1 star with P-rot=2.8 d the long-term activity variations resemble the multi-periodic cycles observed in V711 Tau, owing to high-latitude flux emergence, weak transport effects and stochastic processes of flux emergence.
Keywords: Stars; Activity; Stars: Interiors; Stars: Magnetic Fields; (magnetohydrodynamics:) MUD; Sun: Interior; Sun: Magnetic Fields; Yıldızlar; Aktivite; Yıldızlar: İç Mekanlar; Yıldızlar: Manyetik Alanlar; Güneş: İç; Güneş: Manyetik Alanlar